An interactive immune co-evolutionary design approach for the spinning of differential fibers - Ying-Ying Li; Li-Hong Ren; Yong-Sheng Ding; Kuang-Rong Hao; Xiao Liang; Hua-Ping Wang (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
Co-evolutionary algorithm behaves in a complicated and counterintuitive way for some complex problems. The introduction of interactive immune concept can increase its convergence rate and effectiveness. This paper represents an optimization process of polyester filament in melt spinning with the interactive immune co-evolutionary design approach and also the expert evaluation with entropy-based fuzzy comprehensive evaluation. The simulation results demonstrate its effectiveness. This study also has important value and widespread application prospect regarding the spinning process optimization and the subsequent processing in fiber production lines.